POLA KOMUNIKASI DINAS KEBUDAYAAN, PARIWISATA, PEMUDA DAN OLAHRAGA KABUPATEN INDRAGIRI HILIR DENGAN MASYARAKAT SUKU DUANO DALAM MENGEMBANGKAN BUDAYA FESTIVAL MENONGKAH KERANG - Riski Mainaki Pasesa; Anuar Rasyid (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Cutting shells is an activity to catch shells on the stretch of mudflats of the Indragiri Hilir coast. This unique and rare activity at a glance looks like surfing. Using a board like a real surfboard, but the objects and techniques are far different. This activity was lifted from the culture of the persistent